1995
DOI: 10.1002/nbm.1940080109
|View full text |Cite
|
Sign up to set email alerts
|

Signal changes in gradient echo images of human brain induced by hypo‐ and hyperoxia

Abstract: The effect of hypoxia (inspired oxygen fraction, FiO2 of 10% and 16%) and hyperoxia (FiO2) of 100%) on gradient echo images of the brain using long echo times was investigated in six healthy volunteers (age 24-28 years). Different flip angles were used with an FiO2 of 10% to assess the importance of saturation effects. The total cerebral blood flow was measured by a phase mapping technique during normoxia as well as hypoxia (FiO2 of 10% and 16%) and hyperoxia (FiO2 of 50% and 100%). High relative signal change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
62
0
4

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(70 citation statements)
references
References 20 publications
4
62
0
4
Order By: Relevance
“…Finally, the small CBF change measured in the current study is also at odds with the 16%-27% decrease measured with cardiac-gated VEPC MR imaging. 14,15 Because VEPC images taken of the major vessels near the circle of Willis should represent a reasonable estimate of global supratentorial CBF, 26 more investigation of this apparent discrepancy is warranted. Decreased ⌬M signals were seen in all subjects in all regions of interest during the 100% oxygen inhalation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the small CBF change measured in the current study is also at odds with the 16%-27% decrease measured with cardiac-gated VEPC MR imaging. 14,15 Because VEPC images taken of the major vessels near the circle of Willis should represent a reasonable estimate of global supratentorial CBF, 26 more investigation of this apparent discrepancy is warranted. Decreased ⌬M signals were seen in all subjects in all regions of interest during the 100% oxygen inhalation.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies using cardiac-gated velocity-encoded phase contrast (VEPC) measured global CBF decreases ranging between 16% and 27%, 14,15 greater than that measured with tracer methods. Two previous ASL-based measurements have reported markedly different CBF changes, one measuring a 7% decrease, 11 the other a 33% decrease.…”
mentioning
confidence: 99%
“…An increase in the inspired fraction of oxygen (FiO 2 ) is known to be effective as a contrast agent for T 2 *-weighted magnetic resonance imaging (MRI) (Losert et al, 2002;Rostrup et al, 1995). Unlike injected MRI contrast agents, oxygen has a much faster wash-out time and fewer contraindications.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, it has been demonstrated that when the concentration of deoxyhemoglobin is increased, a decrease in T2 and T2* is anticipated, resulting in a decrease in MR signal intensity in T2-and T2*-weighted images and vice versa. With animal models many investigators demonstrated that BOLD effects can be used to monitor the changes of oxygen saturation in vivo under pathophysiologic conditions, such as hypoxia (Turner et al, 1991;Prielmeier et al, 1994;Jezzard et al, 1994;Hoppel et al, 1993;Rostrup et al, 1995;Kennan et al, 1997;Lin et al, 1998a), hyper-and hypocapnia (Jezzard et al, 1994;Davis et al, 1998;Lin et al, 1999), hemodilution (Lin et al, 1998b), and ischemia (De Crespigny et al, 1992;Ono et al, 1997). However, all of the above studies only focus on relative measurements of cerebral blood oxygen saturation (Y) and little attention has been given as to how an absolute measurement of Y can be obtained with the BOLD effects.…”
mentioning
confidence: 99%